2005
DOI: 10.1021/nl050298x
|View full text |Cite
|
Sign up to set email alerts
|

Detection Limits for Nanoscale Biosensors

Abstract: We examine through analytical calculations and finite element simulations how the detection efficiency of disk and wire-like biosensors in unmixed fluids varies with size from the micrometer to nanometer scales. Specifically, we determine the total flux of DNA-like analyte molecules on a sensor as a function of time and flow rate for a sensor incorporated into a microfluidic system. In all cases, sensor size and shape profoundly affect the total analyte flux. The calculations reveal that reported femtomolar de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
559
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(579 citation statements)
references
References 35 publications
8
559
1
1
Order By: Relevance
“…However, kinetic considerations are particularly important (1) at low concentrations, where detection limits are usually determined [56,57] and (2) when target diffusion to the probe surface takes longer than the binding interaction [58].…”
Section: Probe-target Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, kinetic considerations are particularly important (1) at low concentrations, where detection limits are usually determined [56,57] and (2) when target diffusion to the probe surface takes longer than the binding interaction [58].…”
Section: Probe-target Bindingmentioning
confidence: 99%
“…Madou provided a general treatment of biosensor miniaturization and discusses scaling other varieties of electrical biosensors [107]. It has also been shown that scaling any type of affinity biosensor leads to tradeoffs between settling time and limit of detection [57,108,109].…”
Section: Scaling Electrode Sizementioning
confidence: 99%
“…For this convex electrode geometry, which can be conceptualized as an inverse geometry of the largely concave np-Au geometry, the enhanced sensor performance was attributed to larger deflection angles between grafted probe molecules enabled by small radius of curvature of the electrode nanostructures 16,51,52 . Finally, it should be noted that the sensor discussed in this study was not optimized for lower detection limits and it can be significantly improved by reducing electrochemical cell volume (e.g., via microfluidics) and electrode size to optimize target-to-electrode transport and reaction rates 53,54 . Scheme 1. a) For the un-annealed np-Au with minimal cracks, the molecules (e.g., DNA probes) can permeate the porous films only from the top surface.…”
Section: Target Hybridization On Different Morphologiesmentioning
confidence: 99%
“…Another limitation imposed on the applications of porous silicon optical biosensors is the inefficient analyte transport, i.e., slow diffusion rate of analyte into pores [65,66]. A simple way to deal with it is to change the setup of porous silicon biosensors by flowing analytes through rather than over the sensing device [67].…”
Section: Photonic Crystal Based Biosensingmentioning
confidence: 99%